Strategic Management of Boarding School Based Schools in Improving the Quality of Education at SMA Negeri 2 Plus YPMHB Sipirok - Siregar, Astri Novia; Sugesti, Tutik (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to analyze the implementation of strategic management in the context of boarding school-based schools at SMA Negeri 2 Plus YPMHB Sipirok, with a focus on efforts to improve the quality of education. Strategic management is understood as a series of systematic steps including planning, implementing, and evaluating strategies aimed at optimizing organizational performance. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and document analysis. The results of the study indicate that the school has succeeded in formulating a vision, mission, and goals that are directed at forming students who excel academically, have character, and are competitive. The implementation of strategies based on SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis helps schools identify internal potential and external opportunities to overcome various challenges. Optimization of human resources, finances, and facilities is the main key to supporting the success of the learning process. Teachers and education personnel are given ongoing training to improve their competence. Budget management is carried out efficiently with a priority on improving physical and digital facilities, including dormitory rooms, laboratories, and access to information technology. This study concludes that the implementation of integrated strategic management can improve the quality of education at SMA Negeri 2 Plus YPMHB Sipirok. The recommendations given include strengthening human resource capacity, diversifying funding sources, and improving learning technology to support the sustainability of education quality in boarding school-based schools.